Prediksi Kepuasan Pelanggan pada Layanan E-government Menggunakan Algoritma Decision Tree - Indah Permatasari; Dona Marcelina; Evi Purnamasari (JSAI (Journal Scientific and Applied Informatics), 2025)
The Online Licensing Service Information System (SIPPERI) implemented by DPMPTSP Palembang City aims to enhance efficiency, transparency, and accountability in public services. However, several challenges were reported by users, including unintuitive navigation, slow system responses, and inaccurate information. These challenges impact the level of user satisfaction with the service. This study uses the decision tree algorithm to evaluate user satisfaction based on data obtained through questionnaires with a Likert scale assessment involving 100 respondents. The analysis process uses the Python programming language. The dimensions analyzed include Efficiency (E), Trust (T), Reliability (R), Service (CS), Usability (U), Information Availability (I), and Interaction (SI). The analysis results show that the decision tree algorithm achieves an accuracy rate of 95%. The highest-scoring dimensions were recorded in the indicators Download Speed of Forms (R1: 392) and Accuracy of Instructions (E4: 392). Conversely, the lowest-scoring dimensions were Intuitive Navigation (E1: 300) and Information Availability (I1: 314). This study provides strategic recommendations for DPMPTSP Palembang City to improve dimensions with low scores to enhance user experience and strengthen public trust in e-government services.